Curing kinetics and mechanical properties of cyanate ester/hyperbranched benzoxazine copolymers. (21st January 2022) - Wang, Zhicheng; Li, Runjie; Qin, Qirui; Al Hassan, Mohamadou; Dayo, Abdul Qadeer; Liu, Wenbin; Wang, Jun
Abstract: In the current study, three different curing kinetics models were used to analyze the curing kinetics of hyperbranched benzoxazine (HB‐PED230) and monofunctional benzoxazine (P‐a) modified cyanate ester (CE) resin by non‐isothermal differential scanning calorimeter. Moreover, the effects of two benzoxazines on the copolymerization behavior, thermal stability, and mechanical properties of CE resin were studied. Compared with the P‐a modified CE resin, HB‐PED230 greatly reduces the curing temperature of the copolymer, while improving the bending strength and impact strength. The curing temperature of HB‐PED230 modified CE resin was 79°C lower than neat CE resin, while the CE/P‐a blended resin only reduce 48°C. As the amount of HB‐PED230 increased, the flexural strength and flexural modulus of the copolymers were improved. Surprisingly, when 7 wt% of HB‐PED230 was added, the impact strength of the copolymer was increased by 177.6%, implying that the toughness of CE resin had been greatly improved. Moreover, the fracture morphology of the copolymers was observed by scanning electron microscope. In summary, a small amount of HB‐PED230 blending can effectively improve the overall performance of CE resin.